HUBUNGAN MANAJEMEN WAKTU DENGAN KESIAPAN BELAJAR MANDIRI (SELF DIRECTED LEARNING READINESS) PADA MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS ABDURRAB - Riski Dwi Utami; Ranti Novita Sari; Huda Marlina Wati; Ratih Ayuningtiyas; Olvaria Misfa (LPPM Universitas Abdurrab, 2025)
Problem-Based Learning (PBL) is a learning approach that puts students at the center and exposes students to unsolved problems. One of the important components that is trained and useful in PBL is Self-Directed Learning (SDL) and the important factors in the implementation of the SDL is Self-Directed Learning Readiness (SDLR). Time management is an aspect of self-management that can be assessed in the SDLR. Time management is a way to see how students manage their time to complete tasks and activities well. This study aimed to analyze the relationship between time management and self-directed learning readiness in students in the Medical Education Study Program, Faculty of Medicine, Abdurrab University. This study is observational analytical with a cross-sectional design. The sampling technique was used by stratified random sampling. The total sample in this study is 206. Data analysis uses the spearman rank correlation test.The group of students who have the most high-category time management is in the class of 2020. SDLR is highest in the class of 2022. The correlation test showed a value of p <0.05. The spearman correlation value is 0.642 which means that there is a correlation between time management and the level of self-directed learning readiness. There is a significant relationship between time management and the level of self-directed learning readiness in students in the Medical Education Study Program, Faculty of Medicine, Abdurrab University.